Investigation of nosema apis and nosema ceranae in bees by multiplex pcr in kırıkkale region - Meral Aydenizoz; Ali Can Yorulmaz (Eurasian Journal of Veterinary Sciences)
Aim: The aim of this study was conducted to determine the presence and prevalence of Nosemosis in honeybees in Kırıkkale region by Multiplex PCR. Materials and Methods: Samples were collected from 52 apiaries in Kırıkkale City Center, Bahşili, Balışeyh, Keskin, Sulakyurt and Yahşihan districts. The thorax and abdomen of ten bees collected from every 5 colonies were dissected and crushed with sterile physiological water in a porcelain mortar. The samples with Nosema spores were stained with Saffron and the multiplex PCR was applied to detect specimens to the same samples. Results: Nosema spp. spores were observed in 12 out of 52 apiaries (23.07%) microscopically. Among the positive samples, Balışeyh county was found with the highest rate of 57.14%. The township district is followed by Delice district with 33.33% and Kırıkkale /Center district with a ratio of 23.07%. Nosema spores were not found in samples taken from Bahşili, Keskin, Sulakyurt and Yahşihan districts. In general, the infection rates of the districts were determined as Central (5.76%), Balışeyh (7.69%), and Delice (9.61%). All the positive samples were detected as N. ceranae by multiplex PCR. Conclusion: This is the first study to determine the presence and prevalence of Nosemosis in honey bees in the Kırıkkale region and its etiological agent, N. ceranae. In line with the data obtained in this study, it was concluded that Nosemosis should be taken into consideration in bee losses in the region and beekeepers should be made aware of the issue.